Rizóbios e adubação nitrogenada no desenvolvimento de mudas de mimosa tenuiflora willd. poir. - Freires, Afonso Luiz Almeida (Universidade Federal Rural do Semi-Árido, 2019)
Mimosa tenuiflora Willd. is a species from the Fabaceae botany family, native from Brazil, present in the all Northeast region, with great potential for recovery of degraded soils and nitrogen fixation via symbiotic association with soil-borne bacteria. This study evaluated the effect of rhizobia inoculation and nitrogen fertilization in M. tenuiflora seedlings. The experiment was conducted in greenhouse, in a completely randomized experimental design, 8 treatments: control (yeast mannitol broth); M. tenuiflora isolate; Piptadenia moniliformis isolate; Total Nitro Full® (Bradyrhizobium japonicum); and four ammonium sulfate doses (70, 140, 210, and 280 mg dm-3), with 6 replications each. Effect of treatments on the assessed parameters was analyzed by ANOVA followed by Skott-Knott comparison test at 5 % of probability. Isolated bacteria were classified as Rhizobium sp. based on phenotypic characterization. In most of the assessed parameters, M. tenuiflora isolate was more efficient in promoting seedling growth, with results similar to nitrogen fertilization at 210 and 280 mg dm-3. Piptadenia moniliformis isolate did not improve M. tenuiflora seedlings development.
Monografia
Keywords: Jurema preta; Caatinga; Rhizobium; Fixação biológica de nitrogênio; Jurema preta; Caatinga; Rhizobium; Biological nitrogen fixation; CIENCIAS AGRARIAS::AGRONOMIA